Leituras sobre a condição feminina no Lar dos Vicentinos, em Rio Branco, Acre - Patrícia Carvalho Redígulo (Muiraquitã, 2015)
Resorting to documents collected from medical records, inventories and logs archived in the Hospital of Mental Health of Acre (HOSMAC), as well as data from admission forms and other documents archived in the individual files stored by the St Vincent de Paul Society, this work attempts to open a dialogue with the “silenced” voices of the women who live in the House of the Vincentinians (Lar Vicentino), in the city of Rio Branco, in the Acrean Amazon. The purpose of this dialogue is translating and understanding the senses and meanings of the stories of these women, in the aim of revealing the female condition in specific living conditions, in a refuge within a city which is being promoted as one of the best places in Northern Brazil in terms of quality of life.